Evaluasi Kepuasan Pengguna Terhadap System Application and Product Menggunakan Metode SUS dan PIECES Framework - Mulyono, Andronikus; Nataliani, Yessica (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
User satisfaction with a system is a response to assess the good and bad of a system used in an organization or company. In addition, user satisfaction is also used as a reference for system developers to improve the performance of information systems that have been built. PT XYZ as a company engaged in tea management uses System Application and Product (SAP) oriented Enterprise Resources Planning (ERP) in the form of software to carry out various work activities in the company's business processes. However, there are still various problems of dissatisfaction with the use of SAP software. Because one of the objectives of using the software is to support operations at the company, it is necessary to evaluate with the aim of measuring user satisfaction with SAP. In this research, two methods are used, namely the System Usability Scale (SUS) and the PIECES framework. Based on the research results, the SUS method has a value of 62.79 with the "Okay" category and Grade D, while the results of the PIECES framework method have a value of 3.90 with the Satisfied category and Grade B. This shows that the PIECES method has a value of 3.90 with the Satisfied category and Grade B. This shows that the PIECES framework method has a higher value than the SUS method. Therefore, the application of SAP at PT. XYZ to users needs to be improved again in terms of SAP development, which can be seen from the results of the SUS method which is still considered low.